THE DESCRIPTIVE ANALYSIS OF STUDENTS’ ABILITY IN WRITING REPORT TEXT AT THE TWELFTH GRADE OF SMK NEGERI 1 SITOLU ORI IN 2021/2022 - RATAKAN LAOLI; Yasmina Amaerita Telaumbanua; Hidayati Daeli (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The purpose of the research was to find out and describe the students’ ability in writing report text of SMK Negeri 1 Sitolu Ori. The design of this research was descriptive qualitative research. The total number of the sample was 16 students. The researchers used descriptive qualitative method. The instrument used to get the data was test and interview. Based on the research results from taking students’ worksheet documents and the results of interviews, it is concluded that most of the XII grade students of TKJ SMK Negeri 1 Sitolu Ori are unable to write report texts with an average score of 38 or fail. Based on the data presented in the previous table (tables 4 and 5) and the explanation of the results of the research that there was 1 student (5%) who was included in the sufficient category in writing report texts. On the other hand, there were 10 students (50%) who were not good at writing report texts. Furthermore, there were 5 students (45%) who were included in the category of failing in writing report texts. The results of the study also show that the factors that affect students' ability to write report texts are lack of vocabulary, In addition, finally, based on the findings, it is concluded that XII grade students of SMK Negeri Sitolu Ori have problems in writing report texts The students were not able to express idea.